Analisis Semiotika Charles Sanders Peirce Pada Iklan Telkomsel Semangat Indonesia - Syuhada, Farhan; Thariq, Muhammad (Universitas Muhammadiyah Sumatera Utara, 2024)
An attractive advertising concept that connects products with nuances of beauty, progress, natural wealth, cooperation or mutual cooperation and differences in Indonesia is displayed by Telkomsel. With the theme or title